Decretar: su diversidad pragmática y los poderes del estado en las leyes mexicanas del siglo XIX - Vázquez Laslop, María Eugenia (El Colegio de México, 2026)
This paper analyzes the diversification of the pragmatic values present in the act of decreeing in 19th century Mexican laws, a diversification which reflects the division of the powers of the State. The criteria applied in the analysis are legal and linguistic; particular attention is paid to the illocutionary values of decreeing according to its issuer (whether an individual or a parliamentary body), to its place in the textual structure, and to its grammatical characteristics (person, tense, verbal structure and syntax). 2594 occurrences of decree in legislation from 1810 to 1872 are analysed. Mexican 19th century decrees are shown to exist on various textual levels, some of them contained in others, and to reflect the diversification in other acts of the legislative process of the powers of the State (sanctioning, promulgating or publishing laws), something which is in keeping with the discursive tradition of the 1812 Constitution of Cádiz.